Mathematical models applied to the optimisation of mixtures in the production of silage from coffee by-products - Malta, Marcelo; Cirillo, Marcelo; Fassio, Larissa; Barcelos, Adauto; Lima, Priscilla (Revista Ciência Agronômica, 2016)
The aim of this work was to propose a mathematical model to determine the best combination of the by-products of coffee processing in the production of silage.  To this end, 13 treatments were evaluated, resulting from the combination of wet coffee husks (WCH) and dried coffee husks (DCH), both with and without the use of molasses (M) and with or without the use of the inoculant Lactobacillus plantarum (I). From these components, various mixtures were proposed and evaluated, using the technique of simultaneous optimisation of multiple response variables. Silages with the best characteristics were obtained from the use of 76.40% WCH, 18.77% DCH, 4.83% of M and 0.0001% I.